Comparative analysis of thermally activated building systems in wooden and concrete structures regarding functionality and energy storage on a simulation-based approach. (15th October 2021) - Heidenthaler, Daniel; Leeb, Markus; Schnabel, Thomas; Huber, Hermann
Abstract: Thermally activated building systems (TABS) represent a practicable and energy efficient possibility for heating of buildings. Whereas TABS in concrete structures are well-established, wood-based materials are barely considered. State-of-the-art simulations were conducted for various ceiling structures based on different wood-based materials and concrete regarding the thermal performance. Steady-state simulations demonstrate that TABS in wooden structures are fundamentally functional and able to achieve an appropriate heat flux of 26 W/m² while meeting the comfort requirement of maximum 4 K temperature difference between room air temperature and surface temperature, although considerably higher fluid temperatures are necessary compared to TABS in concrete. The results of transient simulations show that heat storage capacities of up to 1065 Wh/m² can be achieved within the wooden variants compared to 696 Wh/m² for concrete on condition of an equivalent heat flux underneath the ceiling. Furthermore, a combination of different wooden layers within the structure can contribute to both, a comparatively high energy storage potential and a high heat flux density simultaneously, compromising the fact that a higher heat flux density is often accompanied by a lower thermal storage capacity in the simulated models and vice versa. These findings could be used to develop an element of timber as energy storage system. Highlights: Simulation of thermally activated building systems in wooden structures . Represents an innovative utilization of wooden structures . Shows that thermally activated building systems in wood are applicable . Analysis of achievable heat flux density for different wood-based systems . Analysis of thermal storage capacity for various wooden variants and concrete .